A DEEP COMPARATIVE STUDY OF UZBEK AND PERSIAN PROVERBS - Sobirova Shahrizoda Ne’matillaxo’ja qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Proverbs represent one of the most significant elements of folklore and cultural identity in every nation. They embody collective wisdom, social norms, moral values, and historical experience transmitted across generations. This article presents a comprehensive comparative analysis of Uzbek and Persian proverbs from linguistic, semantic, cultural, and pragmatic perspectives. It highlights both structural and meaning-based similarities, differences in stylistic expression, and the role of proverbs in shaping national identity. The study demonstrates that despite belonging to different language families and historical contexts, Uzbek and Persian proverbs reflect universal human cognition and shared moral principles[1] [1] ] Ethnolinguistic Studies of Proverbs, Central Asian Review